Calibration and optimum control of the cascaded three tanks process / Khairiah Amin - Amin, Khairiah (1999)
This is a thesis on calibration and optimum control to the cascaded three tanks process. Both theoretical and practical analysis procedures are included. The theoretical section covers learning of the process and functions of each instrument in the model plant. The practical section covers the calibration of the equipment involves in the process, tuning the controller of the model plant in order to ensure that they are in good working order. Besides the practical section, the optimum tuning of the PID controller using process reaction curve method, ultimate sensitivity method and auto-tuning method for an automatic control of tank level of the model plant will also be covered.